(untitled) (REMUNOM, 2026)
Objective: to map and synthesize evidence on the role of Primary Health Care (PHC) in surveillance, early diagnosis, clinical management, isolation guidance, referral, health education, and professional training related to mpox, with emphasis on the Brazilian context. Method: exploratory scoping review developed in accordance with Joanna Briggs Institute guidance and structured according to PRISMA-ScR. Searches were carried out in national and international databases and complemented by gray literature, with an initial retrieval of 1,000 records and final inclusion of 80 studies and documents. Results: only four studies directly addressed Brazil, revealing a major gap regarding the role of the Family Health Strategy. The literature indicates that PHC can support early detection, triage, reporting, isolation guidance, outpatient management of mild cases, health education, and coordination with other levels of care; however, important barriers persist, including limited access to molecular diagnosis, lack of PHC-specific protocols, stigma, territorial inequalities, and insufficient training. Conclusion: mpox requires more explicit incorporation into Brazilian PHC workflows, with stronger surveillance, continuing education, integration with referral services, and development of tailored operational protocols.